Fundamental research of the solvent role in the ionothermal synthesis of microporous materials - Sun, Xin (Kansas State University, 2012)
Zeolites and zeolite-like materials are a group of porous materials with many applications in industry including but not limited to detergent builders and catalyst in the oil refining and petrochemical industry, due to their unique properties such as uniform pore size, large surface area and ion-exchange capacity. Researchers are constantly seeking new methods to synthesize zeolites. Zeolites are commonly synthesized in water. Then in 2004, a new method called ionothermal synthesis was invented by Dr. Morris and his colleagues, using ionic liquids (ILs) and eutectic mixtures as the solvent. In contrast to water, ILs and eutectic mixtures have negligible vapor pressure, thus making the use of high-pressure vessel unnecessary. In addition, they have various structures which could render new structures to frameworks of zeolite. Furthermore, since the cations of some ILs have structures which are similar to common structure directing agents, they theoretically could be used both as solvent and structure directing agent in ionothermal synthesis, possibly simplifying the synthesis process. This project is aimed at investigating the behavior of precursors of zeolites in ionic liquids and the interaction between precursors and ionic liquids in ionothermal synthesis because these fundamental properties could be useful in the current and future synthesis of zeolites. First, solubilities of different precursors, including Syloid 63 silica particles, aluminium isopropoxide (Al(OiPr)3) and phosphoric acid (H3PO4) in ILs with different structures are reported. Parameters such as activity coefficient and Henry’s constant are calculated from the solubility result. Second, interaction between precursors and ILs are studied. It is found that the addition of ILs in Al(OiPr)3 could change the structure of Al(OiPr)3, especially with the presence of H3PO4. Both ILs’ structures and temperature are capable of influencing the structure change of Al(OiPr)3. Third, hydrochloric acid is used for the first time as the mineralizer to synthesize aluminophosphates in ILs and it could lead to both dense and porous materials. Regardless of the acid used, frameworks synthesized after several hours always undergo a dramatic change after further heating. A slightly longer alkyl chain of ILs could accelerate the formation of crystalline materials. Increasing concentration of precursors in the reaction gel could increase the yield, but the same framework is not retained. Researches have also been done on stability of ILs in the synthesis process and it is found that heat and the presence of H3PO4 could decompose ILs, but the decomposed amount is extremely small.
Keywords: ionothermal synthesis; ionic liquid; zeolite; aluminophosphate; Chemical Engineering (0542)